Effects Of Geological Properties Of Limestone Formation In Blasting - Mohd Ariffin, Muhammad Afiq Ariff (Universiti Sains Malaysia, 2022)
Limestone is a sedimentary rock composed of calcium carbonate (calcite) or calcium and magnesium double carbonate (dolomite). It usually consists of small fossils, shell fragments and other fossil fragments. On careful examination of the rock surface, these fossils are often visible to the naked eye. The grains of some limestones are very fine. Limestone is usually gray, but it can also be white, yellow or brown. It is a soft stone that is easily scratched. It will easily foam in any common acid. The aim of this project is to investigate the effect of geological factors on explosive breakdown at a limestone quarry at Imerys Malaysia in Simpang Pulai, Perak, Malaysia. Because of insufficient knowledge of actual explosive energy released in the borehole, varying initiation practise in blast design, and its effect on explosive energy release characteristic, fragmentation control through effective blast design and its effect on productivity are difficult tasks for practising blasting engineers. The Rock Mass Rating System (RMR) is used to select parameters such as discontinuity length, intact material strength, spacing, weathering, separation and filling. Before the blasting operation began, geological mapping was performed at the bench blasting site to determine the RMR value of the selected site structure, and the strength of the intact material was determined using the Point Load Test (PLT). Rock samples were collected after blasting and fragmentation analysis was performed using WipFrag image processing software. Fraction evaluation data from several blasting series were then compared and correlated with PLT, XRF, and structure data respectively to evaluate the effect of these properties on the resulting fragment size. It was found that the strength of the rock mass, the direction of discontinuity on the slope face and the structural properties of the rock mass at the blast site influence the size of the fracture. As a conclusion of the project, RMR plays a significant role in determining the rock fragmentation analysis following the blast. The mapping data, such as the presence of cracks, weathering, spacing, and infilling, is critical for performing the RMR analysis. RMR analysis is an excellent medium for investigating the condition of a location and determining the type of rock present.